2011
DOI: 10.1111/j.1551-2916.2011.04982.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Microbeads as Adsorbents for Purification Technologies with High Specific Surface Area, Adjustable Pore Size, and Morphology Obtained by Ionotropic Gelation

Abstract: In this study, we present an ionotropic gelation route for obtaining porous alumina/silica microbeads (MBs) with tailorable morphology, specific surface area (SBET), and pore size, which can directly be sintered into porous, monolithic adsorbents (MAds). After sintering, SBETs from 20 m2/g up to 70 m2/g with open porosities up to 90% could be achieved depending on the silica nanoparticle addition. Due to the significantly increased SBET, a more than 100‐fold faster uptake of model dye molecules was obtained. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…Sintering at 1200°C for 1 min resulted in a S BET of 58 m 2 g À1 , which is %57% higher compared to the conventionally sintered MAds. Klein et al [12] showed that conventionally sintered alumina/silica microbeads did not show second phase formation (e.g., mullite) at 1200°C, which was also not observed for rapidly sintered MAds (data not shown). Mesopores in the range of 5-50 nm were found.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Sintering at 1200°C for 1 min resulted in a S BET of 58 m 2 g À1 , which is %57% higher compared to the conventionally sintered MAds. Klein et al [12] showed that conventionally sintered alumina/silica microbeads did not show second phase formation (e.g., mullite) at 1200°C, which was also not observed for rapidly sintered MAds (data not shown). Mesopores in the range of 5-50 nm were found.…”
mentioning
confidence: 87%
“…[7,8] Subsequently their application in filtration is limited to gases and small molecules. [12] These microbeads exhibited a S BET of up to 37 m 2 g À1 and a bimodal pore size distribution at 14 and 40 nm when conventionally sintered at 1000°C. [9] However, these materials exhibit often low specific surface areas, [10] which are disadvantageous for the adsorbents' efficiency.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The most important application areas for ZrO 2 include toughened ceramics [2,3], refractories [4], piezoelectrics [5], solid electrolytes [6], active component and/or supports in catalysis [7,8], and photonics [9]. The crystal structure of ZrO 2 has a substantial influence on its characteristics and applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is a very recent finding that large silica beads in the range of 2 to 4 mm with a bimodal pore system including leaching-based pores between 20 and 120 nm as well as additional pores with diameters between 1 to 50 mm can be synthesized via ionotropic gelation 31 of a phase separable sodium borosilicate glass followed by subsequent thermal and leaching treatment. 32 The synthesis route is presented in Fig.…”
Section: Ionotropic Gelationmentioning
confidence: 99%